Smart Port Management in Digital Transformation: A Review for Future Research - Syafrie Muhammad Hawari; Triana Rahajeng Hadiprawoto; Ira Iriyanty; Yeshika Alversia; Soni Adiyono (International Journal of Marine Engineering Innovation and Research, 2024)
Ports are basic center points in worldwide transportation, affecting supply chains and national economies. With the rise of Industry 4.0, joining computerised change such as IoT, huge information, cloud computing, and AI into harbour operations has ended up progressively vital. This study provides a systematic evaluation of 41 selected articles focusing on three critical aspects of smart port development: developments in digital transformation, assessment of smart port implementation, and related challenges and limitations. Utilizing indicators such as technology relevance, operational efficiency, user experience, regulatory barriers, and infrastructure readiness, the analysis reveals that a significant number of articles contributed to digital transformation technologies (average score: 7.61), performance evaluation (average score: 6.63), and challenges and barriers (average score: 6.15). Trend graphs and Pareto diagrams highlight fluctuations in contributions and emphasize that a small number of high-scoring articles have a considerable impact. This research underscores the importance of a thorough and systematic approach in assessing digital transformation technologies and offers valuable insights into the current landscape, opportunities, and challenges. The findings are intended to guide stakeholders in developing effective strategies for achieving sustainable digital transformation in smart ports.